Prospects and expectations of ehealth services in north-lima from mathematical modeling and computational simulation - Nieto Chaupis, Huber (2015)
We present a study of the expected advantages of application of eHealth services like telemedicine in non-urban zones located over the north part of Lima city. Essentially, this paper is focused on the fact how type-2 diabetes mellitus (DMII) and tuberculosis (TB) are spreading into a specific human group it how it might be alleviated with modern concepts of applications of eHealth technologies like telemedicine. In order to extract the most representative patterns a survey data collection was applied up to 50 families which were randomly selected. This information has served to simulate 1000 individual samples through the usage of the Monte Carlo algorithm. The simulated statistics in conjunction to the telemedicine methodologies enter into a mathematical formulation based on success probabilities and efficiencies. The resulting calculations allow us to analyze the possible scenarios with and without teleconsults in order to compare and establish the expected advantages of eHealth. Under certain circumstances of network connectivity, well-trained health care specialists and appropriate implementation of softwarehardware interfaces, interesting prospects to reduce mortality rate as well as economic-social costs attributed to TB and DMII in those peri-urban zones located in north-Lima have been identified. According to the predictions from this study, the expectancy of life can be enlarged in up to a 25±5% and 10±3% of their nominal values for patients with diagnostic of TB and DM-II, respectively.